Exploring Stakeholder Perceptions to Enhance Municipal Reputation: A Quantitative Study of Amahlathi Local Municipality, South Africa - Pikolomzi Qaba; Bongani I Dlamini (New Advances in Business, Management and Economics Vol. 5, 2025)
Service delivery protests have become increasingly violent in South Africa over the past decade, highlighting the pressing need for effective municipal reputation management. The Amahlathi Local Municipality has faced intense criticism for mismanaging funds, lacking oversight and accountability, and failing to provide basic services to its electorate. This study undertakes an empirical analysis of Amahlathi Local Municipality’s (ALM) reputation among its stakeholders, addressing the scarcity of research on municipal reputation management in South Africa. Utilizing a quantitative methodology, a questionnaire was distributed to 383 citizens in ALM, yielding a response rate of 85.64% (328 respondents). The data was analyzed using descriptive statistics and inferential analysis (factor analysis and regression), revealing significant disparities between stakeholder expectations and perceived performance of ALM. The findings highlight key factors influencing municipal reputation, including service delivery, communication, and accountability. Notably, ALM’s reputation is compromised by inadequate service delivery, particularly in areas such as water and sanitation, roads, and waste management. These results contribute significantly to the understanding of municipal reputation management in South Africa, emphasizing the importance of stakeholder engagement and effective service delivery. This research contributes theoretically, practically, and policy-wise. Theoretically, it advances knowledge on municipal reputation management in South Africa. Practically, it informs ALM’s strategic planning and stakeholder engagement. Policy-wise, it highlights areas for improvement in service delivery and governance. The study’s methodology comprised questionnaire design adapted from existing municipal reputation frameworks, random sampling of ALM citizens, and data analysis using descriptive statistics, factor analysis, and regression. The study concluded that reputation management or branding is increasingly important for public organizations. It has much to do with social accountability, meaning that an organization, often without a formal obligation to do so, tries to provide information and justify its actions to various audiences. The point of departure in this study was to investigate ALM and the factors that affect how it manages its reputation. However, much research on the significance of corporate reputation management has been within the private sector, with limited research on its impact on the public sector, particularly in the developing world.